INFLUENCERS’ CONTAGION EFFECTS IN SOCIAL MEDIA - Abstract - Shuqair, Saleh (2021)
Shuqair, S., Alves, R., Pinto, D. C., & Mattila, A. (2021). INFLUENCERS’ CONTAGION EFFECTS IN SOCIAL MEDIA - Abstract. In Proceedings of the European Marketing Academy, 50th (pp. 1-2). European Marketing Academy (EMAC). http://proceedings.emac-online.org/pdfs/A2021-94542.pdf